The Influence Of E-Service Quality And E-Recovery On E-Satisfaction And Its Implications For E-Loyalty Of Shopee User In Indonesia - Syafriani, Mona; Dini Hidayah (Jurnal Ilmiah Ekonomi Dan Bisnis, 2025)
E-service quality and e-recovery are investigated in this research to determine their influence on e-satisfaction and the resulting effect on e-loyalty among Shopee users in Indonesia. Employing a quantitative survey approach, the study involved 384 participants selected via simple random sampling, with sample size determined following Krejcie and Morgan’s guidelines. Data was gathered through a combination of online and offline surveys to ensure representativeness. The results of hypothesis testing indicate that e-service quality and e-recovery have a significant and positive effect on both e-satisfaction and e-loyalty, supported by t-statistics exceeding the threshold of 1.96. Furthermore, e-satisfaction functions as an important mediator linking e-service quality and e-recovery to e-loyalty, also supported by t-values exceeding 1.96. These results highlight the critical role of delivering superior electronic services and implementing effective recovery mechanisms to enhance customer loyalty on e-commerce platforms like Shopee. The study provides meaningful insights for Shopee’s management to improve customer satisfaction and loyalty by optimizing service quality and complaint efficiently and effectively.